2009
DOI: 10.1177/1090198108324597
|View full text |Cite
|
Sign up to set email alerts
|

Seriously Mentally Ill Women’s Safer Sex Behaviors and the Theory of Reasoned Action

Abstract: Seriously mentally ill women at risk for HIV infection (n = 96) participated in structured interviews assessing sexual and substance use behavior over a 3-month period. The majority of the women (63.5%) did not use condoms. Consistent with the Theory of Reasoned Action, condom use attitudes and perceived social norms about safer sex were associated with safer sex intentions. Supplementing TRA variables with safer sex self-efficacy explained additional variance in safer sex intentions. Greater safer sex intenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
3
2
Order By: Relevance
“…Our findings are most similar to those found by Randolph and colleagues who examined the social support networks of chronically mentally ill women (ages 19-63). Randolph et al, defined social support network as individuals they would "talk to for advice or about things that are very personal, private, and related to health" and found that their mean size of social support networks was 1.98 (standard deviation of 1.38) (Randolph et al, 2007). They found that 11.2% reported having no social support network (Randolph et al, 2007), compared with 17.3% in our sample.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Our findings are most similar to those found by Randolph and colleagues who examined the social support networks of chronically mentally ill women (ages 19-63). Randolph et al, defined social support network as individuals they would "talk to for advice or about things that are very personal, private, and related to health" and found that their mean size of social support networks was 1.98 (standard deviation of 1.38) (Randolph et al, 2007). They found that 11.2% reported having no social support network (Randolph et al, 2007), compared with 17.3% in our sample.…”
Section: Discussioncontrasting
confidence: 51%
“…Randolph et al, defined social support network as individuals they would "talk to for advice or about things that are very personal, private, and related to health" and found that their mean size of social support networks was 1.98 (standard deviation of 1.38) (Randolph et al, 2007). They found that 11.2% reported having no social support network (Randolph et al, 2007), compared with 17.3% in our sample. The mean size of social support networks was higher in the three studies of drug-using adults (ranged from 6.8 to 6.9) than our study (Latkin, Forman, Knowlton, & Sherman, 2003;Latkin et al, 1995;Owens & McCrady, 2014).…”
Section: Discussioncontrasting
confidence: 51%
“…Studies with people with disabilities or staff and key informants report relatively high rates of unsafe sex and other risk behaviours including substance use, transactional sex, and reported incidence of previous sexually transmitted diseases (Blanchett, 2000;Brown et al, 1997;Cambridge, 1996;Carey et al, 1997;Carey et al, 1999;Carey et al, 2001;Carey et al, 2004a;Chandra et al, 2003;Choquet et al, 1997;Chopra et al, 1998;Chuang & Atkinson, 1996;Collins et al, 2008a;Collins et al, 2008b;Davidson et al, 2001;Devieux et al, 2007;Gordon et al, 1999;Grassi et al, 1999a;Grassi et al, 1999b;Kalichman et al, 1994;Katz et al, 1994;Kelly et al, 1992; M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 14 1995; Maart & Jelsma, 2010;Meade & Sikkema, 2007;Meade & Sikkema, 2005;Menon & Pomerantz, 1997;Menon et al, 1994;Myer et al, 2009;Ogunsemi et al, 2006;Olaleye et al, 2007;Otto-Salaj et al, 1998;Randolph et al, 2009;Rohleder, 2010;Smit et al, 2006;Susser et al, 1995;Thompson, 1994;Touko et al, 2010;Vanable et al, 2007;Weinhardt et al, 1998;Walkup et al, 1999).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…According to the literature, paying more attention to sex education in patients with severe mental illness is recommended. Risky behaviours and substance uses are some risk factors that make these patients prone to sexually transmitted diseases (STD) [4,8,23,24,31,32,35,43]. A recent study in Ethiopia presents some predictors for risky behaviours in these patients including, male gender, illiteracy, bipolarity, history of hospitalization, perceived internal stigma and poor social support [10].…”
Section: Introductionmentioning
confidence: 99%